Application Design Resume Medical By Using Microsoft Visual Basic.Net 2010 At The Health Center Appointments - Samsir; Syaiful Zuhri Harahap (Publisher Cv. Inara, 2020)
In implementing health services, puskesmas must document all actions and treatments that are given to patients in a document called Medical Records. According to Minister of Health Regulation No.269 / MENKES / PER / III / 2008 article 1 (1), medical records are files containing notes and documents about patient identities. Medical records are of good quality if the medical record is accurate, complete, trustworthy, valid and timely. One form of management in Medical Records is reporting. According to Minister of Health Regulation No.269 / MENKES / PER / III / 2008 article 1 (1), Medical Record is a file that contains notes and documents about patient identity, examinations, actions, and other services that have been given to patients. In the statement, all information about a patient has been reflected which will be made the basis for determining further actions in services and other medical actions given to a patient who comes to the community health center. The Medical Record is said to be of high quality if the Medical Record is accurate, complete, trustworthy, valid and timely. The Medical Record Installation has activities such as registration, data processing, and storage. One form of processing data in medical records is the existence of assembling activities. Assembling is an assembling activity compiling empty Medical Record forms and storing them into Medical Records, ready to use neatly arranged both in terms of quality and quality.